6-Mercaptopurine complexes with silver and gold ions: Anti-tuberculosis and anti-cancer activities - Cuin, Alexandre; Massabni, Antonio Carlos [UNESP]; Pereira, Guilherme Alves; Fujimura Leite, Clarice Queico [UNESP]; Pavan, Fernando Rogerio [UNESP]; Sesti-Costa, Renata; Heinrich, Tassiele Andrea; Costa-Neto, Claudio M. (Elsevier France-editions Scientifiques Medicales Elsevier, 2011)
Synthesis, characterization and biological studies of silver and gold complexes with 6-mercaptopurine (H2MP) are described. The Ag(I) and Au(I) complexes with HMP-, AgHMP and AuIHMP, were obtained by mixing an acidified H2MP aqueous solution with an equimolar aqueous solution of AgNO3 or Au(CN)2. The Au(III) complex with HMP-, AuIIIHMP, was obtained by adding an aqueous solution of K(AuCl4) to an acidified H2MP aqueous solution (1: 1 molar ratio) and the final solution was acidified with HCl to pH = 1.0. The Au(III) MP complex, KAu(MP)2, was obtained by adding an aqueous solution of K(AuCl4) to a basic H2MP solution (M: L - 1: 2 molar ratio). Formulas for the complexes are: (Ag[C5H3N4S])*H2O for AgHMP, (Au[C5H3N4S]) for AuIHMP, (Au[C5H3N4S][Cl]2)*2H2O for AuIIIHMP and K(Au[C5H2N4S]2)center dot 2H2O for KAu(MP) 2. The AuIHMP and KAu(MP) 2 complexes decreased cell viability of HeLa cancer cells in vitro. The IC50 values for AuIHMP and KAu(MP) 2 are 3.0 and 30.0 mu M, respectively. Anti-M. tuberculosis assays showed a MIC value of 2.24 mu M for AuIHMP and 5.12 mu M for free MP while AgHMP is active at the concentration 93.2 mu M. (C) 2011 Elsevier Masson SAS. All rights reserved.
Keywords: Silver; Gold; Mercaptopurine; Tuberculosis; Arthritis; Cancer